2013
DOI: 10.1016/j.jtcvs.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Fluid management during video-assisted thoracoscopic surgery for lung resection: A randomized, controlled trial of effects on urinary output and postoperative renal function

Abstract: In patients undergoing video-assisted thoracoscopic surgery, intraoperative urinary output and postoperative renal function are not affected by administration of fluids in the range of 2 to 8 mL/(kg · h). The clinical practice of administering fluids to enhance diuresis in the perioperative period should therefore be abandoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 21 publications
3
35
0
1
Order By: Relevance
“…Understandably, given the absence of trials primarily investigating the effects of urine output as a target, to account for all the possible sources of heterogeneity within the currently available literature would be impractical and the inability to do so is currently an inevitable limitation. However, after acknowledging this limitation, our findings are currently the only assessment of the effects of targeting urine output on mortality, and are supported by the observations from various trials [ 6 , 59 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Understandably, given the absence of trials primarily investigating the effects of urine output as a target, to account for all the possible sources of heterogeneity within the currently available literature would be impractical and the inability to do so is currently an inevitable limitation. However, after acknowledging this limitation, our findings are currently the only assessment of the effects of targeting urine output on mortality, and are supported by the observations from various trials [ 6 , 59 ].…”
Section: Discussionsupporting
confidence: 71%
“…However, a suboptimal hemodynamic status is not always the cause of oliguria. In recent years, the concept of an association between intraoperative urine output and postoperative acute kidney injury has been challenged [ 4 6 ]. As a result, advocacy for permissive oliguria has increased, for example to include permissive oliguria in the early recovery after surgery (ERAS) protocols [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sachin's study demonstrated that intraoperative urine output was not an independent predictor of acute renal failure for non-cardiac surgery patients whose previous renal function was normal (14). Similarly, in VATS lung resection patients, a study found that intraoperative urinary output and postoperative renal function were not affected by the administration of fluids (15). Thus, except in patients with previously abnormal renal function or for whom fluid management is crucial, such as pneumonectomy, placing a urinary catheter to monitor perioperative urine output is not recommended (11).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive fluid overload is a key factor leading to pulmonary edema and lung injury (30). Shedding of the endothelial glycocalyx in response to atrial natriuretic peptide release brought on by hypervolemia and mechanotransduction of the glycocalyx in response to capillary shear stress may be some of the underlying mechanisms to explain the harmful effects of overhydration (31).…”
Section: Eg and Overhydrationmentioning
confidence: 99%